2020
DOI: 10.1016/j.ijsolstr.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A full-field crystal-plasticity analysis of bimodal polycrystals

Abstract: A full field crystal plasticity modelling of bimodal polycrystals is presented. Bimodal polycrystals are generated using a controlled Laguerre-Voronoi algorithm and a modified phenomenological law is used to take into account the grain size effect through a Hall-Petch term. A focus is particularly made on the effects of grain size and of grain size ratio between ultrafine grains and coarse grains populations on local and global mechanical responses. The effect of the spatial distribution of the coarse grains (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…As orientation assignment is typically treated as a post-processing step in microstructure generation, it is possible to couple the proposed algorithm with well-established microstructure generators [21][22][23]. With this modular structure, it is possible to use TOP for generating polycrystalline representations for a variety of applications [94,95]. As an additional benefit, for generating orientations, the TOP method requires only nine (or 22 variables, depending on the highest texture coefficient rank considered) to be stored, contrasting with methods that rely on the entire experimental database.…”
Section: Discussionmentioning
confidence: 99%
“…As orientation assignment is typically treated as a post-processing step in microstructure generation, it is possible to couple the proposed algorithm with well-established microstructure generators [21][22][23]. With this modular structure, it is possible to use TOP for generating polycrystalline representations for a variety of applications [94,95]. As an additional benefit, for generating orientations, the TOP method requires only nine (or 22 variables, depending on the highest texture coefficient rank considered) to be stored, contrasting with methods that rely on the entire experimental database.…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated by EBSD scans presented therein, CG are commonly observed to be embedded in the matrix of FG as isolated inclusions. Previous numerical analyses [20] have shown that in such a configuration of isolated CG, a domain containing at least 9 CG should be considered to obtain quantitatively representative macroscopic properties; yet a 2D domain containing a single CG could provide qualitativaly representative properties, especially for the analyses of local CG-FG interactions. This is the retained configuration of study in this paper, also motivated by the reduction in computational resources and the comfort of analysis it provides.…”
Section: Materials and Microstructurementioning
confidence: 99%
“…for CG and FG families and a unimodal microstructure containing 256 grains and with a mean GS corresponding to either CG or FG. They result from Laguerre-Voronoi tessellations with specific settings on the nucleation and growth processes [20,23]. The Neper software was used to generate these microstructure and to obtain the finite elements meshes [24,25].…”
Section: Materials and Microstructurementioning
confidence: 99%
See 2 more Smart Citations